Understanding the social aspects of earthquake early warning: A literature review - Tan, Marion Lara; Becker, Julia S.; Stock, Kristin; Prasanna, Raj; Brown, Anna; Kenney, Christine; Cui, Alicia; Lambie, Emily (Frontiers in Communication, 2022)
Earthquake early warning (EEW) systems aim to warn end-users of incoming ground shaking from earthquakes that have ruptured further afield, potentially reducing risks to lives and properties. EEW is a socio-technical system involving technical and social processes. This paper contributes to advancing EEW research by conducting a literature review investigating the social science knowledge gap in EEW systems. The review of 70 manuscripts found that EEW systems could benefit society, and the benefits may go beyond its direct function for immediate earthquake response. The findings also show that there are social processes involved in designing, developing, and implementing people-centred EEW systems. Therefore, social science research should not just be concerned with the end-user response but also investigate various stakeholders’ involvement throughout the development process of EEW systems. Additionally, EEW is a rapidly evolving field of study, and social science research must take a proactive role as EEW technological capacities improve further and becomes more accessible to the public. To improve EEW effectiveness, further research is needed, including (1) advancing our understanding of why people take protective action or not, and ways to encourage appropriate action when alerted; (2) enhancing public understanding, investigating best practices for communicating, educating, and engaging with the public about EEW and overall earthquake resilience; and (3) keeping up with technological advances and societal changes and investigating how these changes impact communities’ interactions with EEW from various standpoints including legal perspectives.